Feeding and swallowing outcomes following mandibular distraction osteogenesis: an analysis of 22 non-isolated paediatric cases. Issue 7 (July 2022) - van der Plas, P.P.J.M.; Streppel, M.; Pullens, B.; Koudstaal, M.J.; Mathijssen, I.M.J.; van Heesch, G.G.M.; Wolvius, E.B.; Joosten, K.F.M.
Abstract: Patients with mandibular hypoplasia and upper airway obstruction are at an increased risk of feeding and swallowing difficulties. Little has been described regarding these outcomes following mandibular distraction. The aim of this study was to evaluate the effect of mandibular distraction on feeding and swallowing function. A retrospective study was performed on 22 patients with non-isolated mandibular hypoplasia and severe upper airway obstruction treated with mandibular distraction. Median age at first mandibular distraction was 3.1 years (interquartile range 2.3–6.0 years) and the median follow-up time was 3.5 years (interquartile range 2.0–9.4 years). Prior to mandibular distraction, feeding difficulties were present in 18 patients. Swallowing difficulties were present in 20 patients, all of whom had problems in the oral phase of swallowing, while 11 patients had additional problems in the pharyngeal phase. Following mandibular distraction, at the time of follow-up, feeding difficulties persisted in 13 patients. Swallowing difficulties in the oral phase remained present in all 20 patients, while pharyngeal phase problems persisted in seven patients. In conclusion, feeding and swallowing difficulties are highly prevalent in non-isolated patients and often persist following mandibular distraction. Moreover, these can be the reason that decannulation cannot be accomplished. Hence, awareness and close follow-up by a specialized speech therapist is of paramount importance.